Management dilemmas in pulmonary arterial hypertension associated with congenital heart disease. (1st August 2018) - Condliffe, R.; Clift, P.; Dimopoulos, K.; Tulloh, R.M.R.
Abstract : There are few randomised controlled data to guide management of patients with pulmonary arterial hypertension associated with congenital heart disease (PAH‐CHD). In this clinical review, common areas of uncertainty in the management of PAH‐CHD are identified, the literature is summarised and discussed and a suggested approach offered for each clinical dilemma.